(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Aim of this paper is to highlights the Mughal Policy of Akbar and Babur. Mughal emperor Akbar implemented many policies during his reign, which also included ’The Mughal Policy’. Abul Fazl says that in order “to soothe the mind of the zamidars, he entered into matrimonial relation with them”. In course of time, Akbar expanded and elaborated this policy. The Mughal were the greatest obstacle in his pursuance of policy against the Hindus. Aurangzeb attempted to destroy the power of the Mughal and annex their kingdoms. The mutual relations of the Mughals and the Rajputs have a great importance in the history of the Mughal period.